SINTESIS SILIKA DARI LIMBAH BOTOL KACA BAHAN KIMIA MENGGUNAKAN METODE SOL GEL - Yani’ Qoriati; Akhmad Al Bari (ALOTROP, 2025)
Chemical glass bottle waste can be used to make silica gel due to its high content of SiO2 composition. The aim of this research is to obtain silica which is extracted from chemical waste from glass chemical bottles and synthesized using the sol gel method. Chemical glass bottle waste can be extracted by alkali fusion. The mass ratio of glass powder: NaOH is 1:3. The calcination process is carried out at 800°C within 4 hours to obtain sodium silicate. Sodium silicate was then synthesized using the sol gel method by reacting with HCl to form a white gel. The gel was then left for 18 hours, then filtered. The resulting precipitate was washed until it reached pH 7. The drying process was in an oven at 80°C for 12 hours. The final product is white silica gel which was characterized using FTIR and XRD. FTIR was used to obtain typical absorption bands, such as the siloxane ring 447.5 cm-1, as well as the symmetric and asymmetric Si-O-Si stretching vibrations, namely 702.11 cm-1 and 1022.31 cm-1 , respectively. The XRD results produced a characteristic peak at 2 theta around 22-25°, which means that the silica gel structure obtained in this study has amorphous properties.  Keywords: Synthesis; silica gel; chemical glass bottle waste